2019
DOI: 10.1002/cssc.201901794
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Electrocatalysts for Efficient Reduction of Carbon Dioxide

Abstract: Two‐dimensional (2D) materials are attractive catalysts for the electrochemical reduction of carbon dioxide reaction (eCO2RR) by virtue of their tunable atomic structures, abundant active sites, enhanced conductivity, suitable binding affinity to carbon dioxide and/or reaction intermediates, and intrinsic scalability. Herein, recent advances in 2D catalysts for the eCO2RR are reviewed. Structural features and properties of 2D materials that contribute to their advanced electrocatalytic properties are summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 195 publications
0
19
0
Order By: Relevance
“…Due to the strong binding of CO to the surface of Pd(111) faces,C Oc an induce an anisotropic growth and shape-directing formation of Pd nanosheets.Hence,wereplaced the W(CO) 6 with the Mo(CO) 6 to synthesize Pd nanocrystals.The SEM images of the samples prepared with Mo(CO) 6 show no nanosheets existed under the same synthesis condition (Figure S9a and S9b). Considering that the decomposition of Mo(CO) 6 to produce CO needs higher reaction temperature, the sample with 2D nanosheet morphology should be prepared at 80 8 8C( Figure S9c and S9d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the strong binding of CO to the surface of Pd(111) faces,C Oc an induce an anisotropic growth and shape-directing formation of Pd nanosheets.Hence,wereplaced the W(CO) 6 with the Mo(CO) 6 to synthesize Pd nanocrystals.The SEM images of the samples prepared with Mo(CO) 6 show no nanosheets existed under the same synthesis condition (Figure S9a and S9b). Considering that the decomposition of Mo(CO) 6 to produce CO needs higher reaction temperature, the sample with 2D nanosheet morphology should be prepared at 80 8 8C( Figure S9c and S9d).…”
Section: Resultsmentioning
confidence: 99%
“…[5] Among them, two-dimensional (2D) nanomaterials exhibit unique electronic and photonic properties,a nd surface interface effects,which significantly improve catalytic properties. [6] Recent studies have shown that 2D ultrathin noble metal (such as Pt, [7] Au, [8] Rh, [9] Pd, [10] and Ru [11] )based nanosheets have been synthesized for various applications.As anew member of 2D materials,metallene is composed of bare metallic elements with atomic thickness,w hich can provide abundant metal active sites,high atomic utilization, and high conductivity,s howing great potential in electrocatalytic reactions and energy conversion. [12] In addition to modifying the morphology of materials,the construction of the defects in nanocrystals,s uch as vacancyd efects,d islocations and grain boundaries,isalso an attractive strategy to affect the catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The desired oxygen content, defect density, electrical conductivity, and thickness associated with exfoliated 2D materials, to be tuned, may be adjusted through voltage/current electrochemical parameters. Both cationic and anionic exfoliation, also intercalations, have been applied schematically in the exfoliation process of the graphite itself [44,45], phosphorous black [46,47] iv A and vA group metals [48,49], transition-metal-dichalcogenides [32,50,51], graphitic-carbon-nitride, transition-metal-oxide [52], metal-organic-framework sheets [53] and MXene [54]. Based upon the type of potential used; electrochemical processes are mainly divided into two forms one is (i) cathodic exfoliation, performed in organic solvents such as Dimethyl sulfoxide (DMSO) and propylene carbonate comprising alkylammonium/lithium salts as electrolyte [16,44,[55][56][57][58][59].…”
Section: Figurementioning
confidence: 99%
“…Hence, converting CO 2 into value-added products is recognized as a promising solution regarding environmental issues brought by the rapid increase of CO 2 emissions, such as global warming, ocean acidification and sea-level rise [1,2]. Unfortunately, the CO 2 molecule is chemically inert with two extremely stable C=O double bonds with the bonding energy of 805 kJ mol À1 [3][4][5]. Hence, conventional thermal catalytic conversion would consume enormous energy.…”
Section: Introductionmentioning
confidence: 99%